ANNUAL REPORT ON THE WORK OF THE CENTRAL INLAND FISHERIES RESEARCH STATION FOR THE YEAR 1952-53 - Mandapam, Central Marine Fisheries Research Statio (Indian Journal of Fisheries, 2016)
THE main work of this section is to solve the numerous difficulties andproblems of the practical pisciculturist with a -view to aid him in producingthe maximum amount offish as food with the minimum of expenditure. Fishseed" or fry of major carps have to be collected every year from rivers in therainy season, conditioned and fed in suitable nurseries until they are fit tobe transported to ponds, tanks and reservoirs, where they are grown untilmarketable.